A Review of the Influence of Vitamin D Deficiency on Muscle Strength and Exercise Performance in Adults - Weronika Popow; Paulina Sadkowska; Katarzyna Jania; Karolina Smolińska; Julia Kulczycka; Michał Ciołkosz; Tomasz Antczak; Monika Gajda-Bathelt; Monika Dąbek; Zuzanna Perlicka (Quality in Sport, 2025)
Background: Vitamin D plays a crucial role in maintaining musculoskeletal health. A growing body of evidence links vitamin D deficiency with decreased muscle strength and suboptimal exercise performance in adults.